Permanent Magnet Assisted Synchronous Reluctance Motor - Knebl, Ladislav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
In these days, there is big emphasis put on electric motors efficiency, the best efficiency can be achieved with surface mounted permanent magnet (SMPM) motor. The SMPM motors efficiency may be even in cases of small machines, higher than 90%. Unfortunately this kind of motor is expensive, because neodymium magnets are used. The synchronous reluctance assisted motor (SRAM) topology is one of many possible machines that might in some cases replace the SMPM machines. Because cheap ferrite magnets are used and still similar characteristics can be achieved.
Keywords: permanent magnet assisted synchronous reluctance motor; permanent magnet synchronous motor; ferrite magnets; permanent magnet; finite element analysis; synchronous reluctance motor